Pengaruh Likuiditas dan Solvabilitas terhadap Kinerja Keuangan (Periode 2013-2018) PT. Gudang Garam Tbk - Rizki Wakhida Kusuma Wardani; Sentot Imam Wahjono; Dahruji Dahruji; Nurullaili Mauliddah (PROCEEDING UMSURABAYA, 2022)
Financial management, or in other literature called spending, is all company activities related to obtaining, using funds, and managing assets by the company's overall goals. Liquidity Ratio is used to measure the company's ability to fulfil its financial obligations that are immediately fulfilled or short-term obligations. Solvency Ratio is a ratio that measures how much the company uses funds from debt (loans).This research aims to determine the effect of liquidity and solvency simultaneously on the financial performance of PT Gudang Garam Tbk, which is listed on the Indonesian stock exchange. The population in this research is the entire financial report of PT Gudang Garam Tbk for the last five years, while the sample is the balance sheet and income statement for five years (2013-2018). The data collection technique used in this research is library research and google study and access to the Indonesia Stock Exchange website (www.idx.co.id). This research indicates that the liquidity variable (X1) has a significant effect on financial performance (Y). While the solvency variable (X2) also has a substantial impact on the financial performance (Y) of PT Gudang Garam TbkÂ Keywords: Service quality; Price; Trust; Intention to purchaseÂ